2009
DOI: 10.1002/pola.23383
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐induced self‐assembly in cardanol‐based urethane methacrylate comb polymers

Abstract: We report side chain urethane-methacrylate comb polymers based on the renewable resource cardanol and its saturated analogue 3-pentadecyl phenol and their self-assembly into pores, spheres, vesicles, tubes, and so forth. The monomers were synthesized in one pot by coupling 1 equiv. of isophorone diisocyanate with 1 equiv. of cardanol/pentadecyl phenol followed by coupling with 1 equiv. of hydroxyethyl methacrylate. They were polymerized free radically using benzoyl peroxide as the initiator and were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…3-pentadecylphenol were incorporated as pendant units to the side chain urethanemethacrylate through hydrogen bondable urethane linkage (Scheme 17) and the authors observed various morphologies such as tubes, spheres, and honeycomb patterns in drop cast lms. 199…”
Section: Addition Monomersmentioning
confidence: 99%
“…3-pentadecylphenol were incorporated as pendant units to the side chain urethanemethacrylate through hydrogen bondable urethane linkage (Scheme 17) and the authors observed various morphologies such as tubes, spheres, and honeycomb patterns in drop cast lms. 199…”
Section: Addition Monomersmentioning
confidence: 99%
“…The unique structure and renewable nature of cardanol make it an ideal raw material to realize the green chemical strategy for chemical industry. Recently, synthesis of cardanol‐based polymers have gained considerable research interest, especially for use in the production of phenolic resins, vinyl resins, biomass‐based materials, polyurethane, and soft nanomaterials . However, despite the projected potentialities of CNSL, only a few have been realized commercially.…”
Section: Introductionmentioning
confidence: 99%
“…A solution of C4-SMe 4H-chromene (6) (0.2 g, 0.4 mmol) and H-cardanol (1) (0.39 g, 1.2 mmol) in EtOH (6 mL) was refluxed for 12 h to provide 2s (0. 23 Hz, 3H), 2.59 (t, J = 7.4 Hz, 2H), 2.43 (t, J = 7.4 Hz, 2H), 1.63-1.52 (m, 4H), 1.27 (br, 48H), 0.9 (t, J = 6.1 Hz, 6H). 13…”
Section: -(2-(methylamino)-3-nitro-7-pentadecyl-4h-chromen-4-yl)-5pementioning
confidence: 99%
“…The 4-aryl-4H-chromene 2s has a polar core with two long chain pentadecyl, non-polar and hydrophobic wings. Such molecules, when properly aggregated, could exhibit liquid crystallinity and the ensuing display characteristics [23].…”
mentioning
confidence: 99%